Design Of Dental Police Patient Service Information System at Upt Puskesmas Talagabodas Bandung: Design Of Dental Police Patient Service Information System at Upt Puskesmas Talagabodas Bandung - Alvat Taupik Hidayat; Ridoy Eka Dharma Sirait (Institute of Computer Science (IOCS), 2020)
The era of globalization and information will have created new standards that must be met by all players in this sector, no exception in the health care sector. The increasingly rapid development of technology also has an impact on all layers of business, whether it be a company, an institution, or an agency that is large or small in scale so that the information system supported by proper data processing is proven to be able to accelerate performance which in the end will generate great benefits for society.This study aims to determine the design description of the information system for dental services at the UPT Puskesmas Talagabodas Bandung. The research methods used in this study are qualitative research methods and data collection techniques, by means of observation, interviews, and web searches. Meanwhile, the software development method used is the waterfall method.From the research that has been carried out, it was found that there are several problems related to the service of polygene patients, (1) Patient care for polygygies is still done manually so that it consumes a lot of time. (3) There is no report for the reference given. Solutions to problems that exist in the current system, including: (1) The need for the development of information systems and data sources regarding information systems services, especially in polygyny services such as the information system that the author designed. (2) It is better if a centralized storage system is to be carried out in order to make it easier to control recorded documents and integrate them with other services (3) Consider and develop a back-up information system to meet each patient's need for service-service activities.